A Counseling Application as an Alternative Tool in Increasing Coping Self-Efficacy Among University Students With Academic Distress During Coronavirus Disease 2019 Pandemic in Indonesia: A Study Protocol for a Randomized Controlled Non-Inferiority Trial - Hinduan, Zahrotur Rusyda; Wedyaswari, Miryam; Reswara, Ilham Phalosa; Setyowibowo, Hari (Frontiers in Psychology, 2021)
The Covid-19 pandemic increased education-related distress among university students globally, including in Indonesia. Psychological factors such as academic demands, limited opportunity to meet their peers, problematic use of technology and domestic problems influenced the well-being of the students, leading to poor academic performance. A mobile-based counselling application was developed to address the distress among university students. The application was meant to reach students living remotely to enable them to access psychological assistance. Therefore, the purpose of this study was to describe a protocol aimed to evaluate the equivalence of the application when compared to the treatment-as-usual (TAU) in increasing students’ coping self-efficacy and resilience as well as decreasing level of depression. A two-armed parallel randomized control non-inferiority trial will be conducted among approximately 50 students with selected academic problems. The participants will be randomly allocated into the TAU and the intervention groups. The primary and secondary outcomes will be measured by Indonesian versions of the Coping Self-Efficacy (CSE) Scale (Chesney et al., 2006), the Resilience Scale (RS-14) (Valentino, 2021), and the Patient Health Questionnaire (PHQ-9) (Onie et al, 2020). Data will be collected at baseline, at the end of each session and after 3 months. The outcomes will be analysed using repeated-measures ANOVAs, intention to treat and per protocol analysis. If proven, the application will be used as the alternative media in helping the students.